Epidemiology and diagnostic of MASLD in Latin America: a yet to be met challenge - Olaez-Ramos, Carolina Elizabeth; Mojica-Zamudio, Karla Lizette; Sandoval-Rodríguez, Ana; Armendáriz-Borunda, Juan (Frontiers in Pharmacology, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD) has emerged as a major global health concern, affecting more than one-third of the adult population worldwide. Notably, Latin America exhibits the highest regional prevalence, with recent estimates of 44.4%. This elevated burden is attributed to the convergence of risk factors that render the population particularly vulnerable. These include high rates of obesity and type 2 diabetes mellitus (T2DM), widespread adoption of energy-dense and nutrient-poor dietary patterns, low levels of physical activity, increased alcohol consumption, and underlying genetic predispositions. Despite its growing impact, MASLD remains significantly underdiagnosed in this region. This is largely due to the limited access to gold-standard diagnostic modalities, such as liver biopsy and magnetic resonance imaging, which are costly, invasive, and often unavailable in routine clinical settings. The lack of accessible diagnostic infrastructure delays early identification and intervention, contributing to disease progression and an increased healthcare burden. Consequently, there is an urgent need to establish cost-effective, non-invasive screening strategies capable of identifying individuals at risk and facilitating timely clinical decision-making. This review synthesizes the current epidemiological data on MASLD in Mexico and Latin America and examines the most validated diagnostic and screening tools currently available.